DYSPHAGIA TOWARDS NUTRIENT INTAKE AND MALNUTRITION CASE IN STROKE PATIENTS: LITERATURE REVIEW - Hafika Yunisari Pradina; Ria Ambarwati (Jurnal Riset Kesehatan, 2020)
Dysphagia is one of the most important clinical manifestations of stroke and can pose a greater risk of malnutrition for patients during and after hospitalization. The purpose of this research is to review the literature about dysphagia on nutrient intake and malnutrition case in stroke patients. Type of the research is literature review which consist of journals cited the incidence of stroke patients suffered Dysphagia from 2015–2020 year of national and international publication. The result of dysphagia people can only consumed 10–33% of nutrient intake during 2 weeks and 3 months at home. This condition is insufficient for the energy and nutritional needs of the patient and can effect malnutrition case due to dysphagia which is 6-78%. The enteral formula can be obtained to reach energy and nutrients by focusing to the stroke patient treatment. Dysphagia experienced by stroke patient will affect nutrient intake and the malnutrition case. The suggestion of this paper is pointed to the health workers and the family of dysphagia people to concern energy and nutrients needs of the patient regularly.